Detection of the novel HLA allele, HLA‐DQA1*01:65, identified in a Danish donor. (12th October 2021) - Hald, Jacob; Plesner, Annette; Hauge, Anne Werner; Bruunsgaard, Helle
Abstract : HLA‐DQA1*01:65 differs from HLA‐DQA1*01:03 in exon 1 at amino acid ‐7 a valine to methionine substitution.